Formulation and characterization of ternary complex of poorly soluble duloxetine hydrochloride - Pinakin Pandya, Narendra Kumar Pandey, Sachin Kumar Singh, Manish Kumar (Journal of Applied Pharmaceutical Science, 2015)
Duloxetine hydrochloride (DXH) suffers from poor solubility and thereby poor absorption, which ultimately leads to poor bioavailability. In present study, an attempt has been made to formulate and characterize duloxetine hydrochloride (DXH) complex, using β-cyclodextrin (β-CD) and different hydrophilic polymers in order to enhance its solubility and dissolution rate. Phase solubility study was used to investigate the interaction of the drug in binary systems (DXH-β-CD) as well as ternary systems (DXH-β-CD-hydrophilic polymer). It was observed that solubilization of DXH by β-CD was further enhanced by using HPMC K4M at 0.1% w/v concentration. Several methods were used to prepare ternary complex of DXH-β-CD-HPMC K4M. Ternary complex prepared by co-evaporation method containing DXH-β-CD-HPMC K4M in the ratio of 1:1.10:0.01 has shown the fastest dissolution rate (53.65 ± 2.83% in 5 min) as compared to pure DXH (3.03 ± 1.88% in 5 min) as well as other methods used to prepare these complexes. The prepared ternary complex system was characterized by the help of X-ray powder diffraction studies, differential scanning calorimetry and scanning electron microscopy. It was observed that enhancement in solubility as well as dissolution rate of DXH was due to formation of ternary complex system.
Keywords: Duloxetine hydrochloride, &beta; -cyclodextrin, HPMC K4M, Ternary complex, Co-evaporation, Characterization.